Prostitución femenina en Quito: actores, perspectiva moral y enfoque médico (primera mitad del siglo XX) [Debates] - Checa Ron, Sophia (2016)
This article investigates prostitutes in Quito, one of the most stigmatized of society during the first half of the twentieth century groups. The paper not only analyzes who these women were, but also their clients and pimps. Then follows the exploration of the Catholic conception of a prostitute as sinful and how medicine constituted the image of diffusion of venereal diseases. On this view, the role played by the Office and Regulation of Venereal Prophylaxis as monitoring and control devices is highlighted.